Dynamic modelling and analysis of 3-axis motion compensated offshore cranes. (3rd April 2018) - Wang, Shenghai; Sun, Yuqing; Chen, Haiquan; Du, Jialu
ABSTRACT: Due to the underactuation of crane systems and the wave-induced ship motions, the payload swing is unavoidable and may put relevant operations in danger. Thus, the compensation system is an essential part of offshore crane to ensure human safety and increase operation efficiency. In this paper, a combined ship motion compensation (CSMC) approach is proposed based on the direct ship motion compensation (DSMC) proposed by Barge Master. The principle and structure of CSMC was introduced. The dynamic models of DSMC and CSMC were established in a uniform manner. Numerical results were included to demonstrate that: first, CSMC can achieve comparable performance as DSMC for payload positioning; second, comparing to DSMC, the maximum total power consumption of CSMC can be reduced by about 80% at sea state 4–6.